Nonobstructive Acute Renal Failure with a Large Solitary Fibroid. (7th June 2016) - Elkattah, Rayan; Mashak, Zineb; Bakker, Blakele; Mohling, Shanti; Yilmaz, Ali; DePasquale, Stephen; Boren, Todd
Abstract : A 38-year-old African American woman presenting with acute abdominal pain and nonobstructive renal failure was found to have an enlarged fibroid uterus. A differential for sepsis was considered. Lab evaluation revealed an elevated creatinine and myoglobin level at 3.9 mg/dL and 2140 ng/mL, respectively. Ongoing hemodynamic instability mandated surgery for acute abdomen. A 25 cm fibroid uterus was extirpated through a total abdominal hysterectomy. Immediate improvement of acute nephropathy mirrored the postoperative decline in serum myoglobin levels. Myoglobinemia from a massive degenerating fibroid is associated with nonobstructive acute renal failure.